2016
DOI: 10.1002/mrd.22734
|View full text |Cite
|
Sign up to set email alerts
|

Screening of reproduction‐related single‐nucleotide variations from MeDIP‐seq data in sheep

Abstract: Extensive variation in reproduction has arisen in Chinese Mongolian sheep during recent domestication. Hu and Small-tailed Han sheep, for example, have become non-seasonal breeders and exhibit higher fecundity than Tan and Ujumqin breeds. We therefore scanned reproduction-related single-nucleotide variations from methylated DNA-immunoprecipitation sequencing data generated from each of those four breeds to uncover potential mechanisms underlying this breed variation. We generated a high-quality map of single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Recently, studies have been conducted to identify the genome-wide methylation profiles of farm animals [ 15 18 ]. Previously, some studies have been conducted to describe DNA methylation for sheep ovary [ 19 22 ], but few reports from the ovarian genome-wide methylation pattern [ 23 ]. WGBS, which allows unbiased genome wide DNA methylation profiling, has allowed us to investigate prolificacy related DNA methylation in unprecedented detail [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have been conducted to identify the genome-wide methylation profiles of farm animals [ 15 18 ]. Previously, some studies have been conducted to describe DNA methylation for sheep ovary [ 19 22 ], but few reports from the ovarian genome-wide methylation pattern [ 23 ]. WGBS, which allows unbiased genome wide DNA methylation profiling, has allowed us to investigate prolificacy related DNA methylation in unprecedented detail [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylated-DNA immunoprecipitation sequencing has also been employed to identify genes for phenotypic traits in domestic animals. To data, there has only been one study reported using this method [58] . In that study, 19 single nucleotide variations and nine candidate genes (ADIPOQ, ABCG1, BRWD1, GRIN2B, METTL6, SIAH2, SLCO2A1, TNIK and UMODL1) were identified as being related to sheep reproductive traits.…”
Section: Reproductive Traitsmentioning
confidence: 99%
“… Demars et al (2013) reported the mutations FecX Gr in Grivette sheep and FecX O in Olkuska sheep associated with the highly prolific phenotype by a genome-wide association analysis. Cao et al (2016) found that nine candidate genes including the well-known FecB mutation played important roles in the variable litter size in Hu and Small-tailed Han sheep through methylated DNA-immunoprecipitation sequencing data. Miao et al (2016) identified a set of differentially expressed genes (e.g., FecB) between low- and high-prolificacy breeds (Dorset vs. Small-tailed Han sheep) through implementing integrated analysis of miRNAs and lncRNAs.…”
Section: Introductionmentioning
confidence: 99%